Proceso enfermero para la prevención de caídas del adulto mayor aplicando la Taxonomía Nanda. Centro Gerontológico Amawta Wasi Samay. Periodo octubre 2023 -febrero 2024 - Amangandi Rea, Erika Lisbeth (2024)
The importance of fall prevention particularly in Latin America and the Caribbean, and specifically in Ecuador, where falls are a significant cause of disability and hospital care in this population. The main objective is to apply the nursing process, based on the NANDA Taxonomy, to prevent falls at the "Amawta Wasi Samay" Gerontological Center during the period from October 2023 to February 2024. To achieve this objective, a quantitative and descriptive, focusing the research on the collection and analysis of data on the frequency of falls and the demographic characteristics of older adults, using the Virginia Henderson model. The study population included 29 elderly residents of the center, selected under specific inclusion and exclusion criteria. Data collection was carried out through a nursing assessment guide based on Virginia Henderson's 14 needs. Nursing diagnoses identified ranged from impaired gas exchange to risk of impaired skin integrity, and personalized care plans were developed in collaboration with a multidisciplinary team. The evaluation of the care plans confirmed a significant reduction in the risk of falls, validating the effectiveness of the applied nursing process. OLDER ADULTS, FALL PREVENTION, NANDA, NURSING PROCESS.